Case Report: Inversion of LMX1B - A Novel Cause of Nail-Patella Syndrome in a Swedish Family and a Longtime Follow-Up - Lindelöf, Hillevi; Horemuzova, Eva; Voss, Ulrika; Nordgren, Ann; Grigelioniene, Giedre; Hammarsjö, Anna (Frontiers in Endocrinology, 2022)
Nail-patella syndrome (NPS, OMIM #161200) is a rare autosomal dominant disorder with symptoms from many different parts of the body, including nails, knees, elbows, pelvis, kidneys and eyes. It is caused by truncating variants in the LMX1B gene, which encodes a transcription factor with important roles during embryonic development, including dorsoventral patterning of the limbs. To our knowledge, inversions disrupting the LMX1B gene have not been reported. Here, we report a family with an inversion disrupting the LMX1B gene in five affected family members with mild but variable clinical features of NPS. Our finding demonstrates that genomic rearrangements must be considered a possible cause of NPS.